Survival in women with MMR mutations and ovarian cancer: a multicentre study in Lynch syndrome kindreds. Issue 2 (26th July 2009) - Grindedal, Eli Marie; Renkonen-Sinisalo, Laura; Vasen, Hans; Evans, Gareth; Sala, Paola; Blanco, Ignacio; Gronwald, Jacek; Apold, Jaran; Eccles, Diana M; Sánchez, Ángel Alonso; Sampson, Julian; Järvinen, Heikki J; et al.
Abstract : Background: Women with a germline mutation in one of the MMR genes MLH1, MSH2 or MSH6 reportedly have 4–12% lifetime risk of ovarian cancer, but there is limited knowledge on survival. Prophylactic bilateral salpingo-oophorectomy (PBSO) has been suggested for preventing this condition. Aim: The purpose of this retrospective multicentre study was to describe survival in carriers of pathogenic mutations in one of the MMR genes, and who had contracted ovarian cancer. Methods: Women who had ovarian cancer, and who tested positive for or were obligate carriers of an MMR mutation, were included from 11 European centres for hereditary cancer. Most women had not attended for gynaecological screening. Crude and disease specific survival was calculated by the Kaplan–Meier algorithm. Results: Among the 144 women included, 81.5% had FIGO stage 1 or 2 at diagnosis. 10 year ovarian cancer specific survival independent of staging was 80.6%, compared to less than 40% that is reported both in population based series and in BRCA mutation carriers. Disease specific 30 year survival for ovarian cancer was 71.5%, and for all hereditary non-polyposis colon cancer (HNPCC)/Lynch syndrome related cancers including ovarian cancer it was 47.3%. Conclusions: In the series examined, infiltrating ovarian cancer in Lynch syndrome had a better prognosis than infiltrating ovarian cancer in BRCA1/2 mutation carriers or in the general population. Lifetime risk of ovarian cancer of about 10% and a risk of dying of ovarian cancer of 20% gave a lifetime risk of dying of ovarian cancer of about 2% in female MMR mutation carriers.